Effects of oxygen-plasma treatment on the structure and optical properties of MgxZn1−xO films. (15th June 2017) - Hwang, J.D.; Chang, Y.C.
Abstract: A Mgx Zn1−x O film was grown on a sapphire substrate using a radio-frequency magnetron sputtering system and then subjected to oxygen-plasma treatment. The effects of the treatment time on the structural, optical photoluminescence (PL), and chemical state properties of the Mgx Zn1−x O films were studied. It was found that the crystal quality improved with treatment time because a longer oxygen-plasma treatment provided more energy to improve the crystal quality. The bandgap increased slightly from 3.654 eV for the as-deposited film to 3.660 eV for 15-min-treated film. The increase in the bandgap was attributed to a decrease in the tensile strain of the film; a linear relationship between the bandgap and the strain was also observed. PL spectra showed that the ultraviolet intensity increased with the treatment time, and the defect emission decreased as the treatment time increased up to 10 min. When the treatment time exceeded 10 min (i.e., for the 15-min-treated film), the defect emission increased significantly. X-ray photoelectron spectroscopy demonstrated that the Mg–O bonding increased from 66% for the as-deposited film to 87% for the 10-min-treated film; however, the Mg–O bonding showed a slight reduction in the 15-min-treated Mgx Zn1−x O film owing to the longer plasma treatment time. The relevant mechanisms were studied.